METHODOLOGY FOR DEVELOPING LOGICAL THINKING AND CREATIVITY IN PRESCHOOL CHILDREN THROUGH GAMING PLATFORMS (Multidisciplinary Journal of Science and Technology, 2026)
This article proposes a practical methodology for preschool settings: selecting developmental targets, mapping them to game mechanics, organizing scaffolding and dialogue, balancing screen-based and off-screen play, differentiating tasks, and assessing progress through observation of strategies rather than only “right answers.” The approach is grounded in evidence-based early learning principles (learning trajectories, guided play, and intentional use of technology), and it emphasizes that the educational value of gaming platforms depends less on “how modern” the tool is and more on how wisely adults structure the experience.